2010
DOI: 10.1111/j.1467-9922.2009.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociolinguistic Variation in the Speech of Learners of Chinese as a Second Language

Abstract: With Chinese native-speaker data as the baseline, this study investigates the use of the morphosyntactic particle DE ( ) by learners of Chinese as a second language. The general patterns are as follows: (a) DE tends to be deleted more in informal speech than in formal settings; (b) higher proficiency and longer residence in China-more interactions with native speakers-promote DE deletion; and (c) females tend to adopt more formal language style and use DE more than males. The study also found that teachers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 40 publications
6
30
0
2
Order By: Relevance
“…Such information may have implications for pedagogy. Chinese instruction for native English speakers could focus more on non‐L1‐like, Chinese conceptual patterns and ways of thinking that are different from English, in particular, explicit instruction on L2 speech and writing patterns in Chinese that have been shown to be extremely difficult for nonnative speakers of English to acquire because they do not conform to any rules or sequential patterns present in English (Li, , ). It has been proposed that profiling aptitudes could help match learners to instructional options and pedagogical tasks that would improve comprehension and production (Robinson, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Such information may have implications for pedagogy. Chinese instruction for native English speakers could focus more on non‐L1‐like, Chinese conceptual patterns and ways of thinking that are different from English, in particular, explicit instruction on L2 speech and writing patterns in Chinese that have been shown to be extremely difficult for nonnative speakers of English to acquire because they do not conform to any rules or sequential patterns present in English (Li, , ). It has been proposed that profiling aptitudes could help match learners to instructional options and pedagogical tasks that would improve comprehension and production (Robinson, , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have examined pragmatics among L2 learners of Chinese (Hong 2011;Li S. 2012;Li, X. 2010;Zhang and Yu 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Li () investigated the use of standard emphatic particle DE in the in‐class speech of Mandarin‐as‐a‐second‐language teachers. She found that the teachers used DE more frequently than did a small group of Mandarin native speakers recorded during semi‐directed informal interviews, reflecting the greater level of formality associated with the classroom context.…”
Section: Research On Sociolinguistic Variation In Teacher Speechmentioning
confidence: 99%
“…What the above research indicates is that some studies have begun to consider the connection between the teachers’ out‐of‐class frequency of variant use and the global frequencies found in the general population (Gervais et al., ; Poplack, ) and other studies have begun to investigate variant choice by language teachers in the classroom (Jia & Bayley, ; Li, ). However, other than our previous research, none of these studies has examined teachers’ variant choice in reference to the social marking of the variants in the wider community—they simply used global frequencies or no norms of reference at all.…”
Section: Research On Sociolinguistic Variation In Teacher Speechmentioning
confidence: 99%
See 1 more Smart Citation